Effectiveness of an optimized training using force-velocity profile analysis - Jimenez-Reyes, P.; Samozino, P.; Cuadrado-Penafiel, V.; Brughelli, B.; Morin, J.-B. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
AIM: Ballistic performances, notably jumping, are key factors in many sport activities. They are mostly determined by the maximal power (Pmax) that lower limbs can generate but also by the individual Force-velocity (F-v) mechanical profile characterizing the ratio between maximal force and maximal unloaded extension velocity capabilities. An individually optimal F-v profile has been shown to characterize the best balance between force and velocity capabilities (Samozino et al 2012, 2013). A F-v imbalance Fv _IMB) being associated to lower performances. The F-v profile could be sensitive to specific and optimized training in order to improve ballistic performances. So training has to aim at increasing Pmax and/or optimizing the F-v profile Thus, the aim of this study was to determine the effects of an individual specific force-velocity profiling based-training. METHODS: Sixty-three subjects were assigned to three groups according to Fv _IMB classification: a velocity and a force imbalance deficit groups and a control group (no consideration of Fv _IMB). Mean push-off force, velocity and power were calculated from jump height (Samozino´s method, 2008). From this data, actual and optimal F-v profiles were computed for each subject to quantify Fv _IMB and organize groups accordingly. Participants underwent a 9-week specific resistance training program designed according to Fv _IMB classification to reduce imbalances for the intervention groups versus a one-size-fits-all program with no Fv _IMB consideration for the control group. RESULTS: A greater increase in jump performance (16.6% and 13.3% in force and velocity groups, respectively) was observed in the intervention group, with a decrease in Fv _IMB (-38.3% and -83.2% in force and velocity groups, respectively) compared to controls. CONCLUSION: An optimized and individualized training program specifically addressing the force/velocity imbalance is more efficient in improving jumping performance than a traditional resistance training common to all subjects, regardless of their force/velocity imbalance and optimal force-velocity profile. Thus, Fv _IMB could be considered as a potentially useful variable for prescribing optimal resistance training to improve ballistic (e.g. jumping) performance.